The Effect of Emotional Intelligence and Logical-Mathematical Intelligence on Accounting Understanding with Confidence as a Moderating Variable - Mukti Pinanggio; Suyanto; Gustin Padwa Sari (Future Science, 2022)
This study aimed to analyze emotional intelligence and mathematical logical intelligence on accounting understanding with self-confidence as a moderating variable. The type of research used in this study was quantitative. In this study, the researcher undertook the primary data through questionnaires with a population of 268 students. The sampling technique used purposive sampling with several criteria obtained from 134 respondents. The data were analyzed by MRA (Moderated Regression Analysis) interaction test. The results of this study yielded that emotional intelligence affects accounting comprehension. Logical mathematical intelligence affects accounting understanding, and self-confidence does not moderate emotional intelligence towards accounting understanding, and self-confidence does not moderate logical-mathematical intelligence towards accounting understanding in students.